ANALISIS KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO SYARIAH VS KONVESIONAL, STUDI KOMPARATIF - Irmawati, Irmawati (Taksasila Edukasi Insani, 2025)
This study aims to conduct a comparative analysis of the financial performance of Islamic Microfinance Institutions (LKMS) and conventional microfinance institutions in terms of profitability, liquidity, and risk management. This study seeks to identify the advantages and challenges faced by each financial system in managing financing for the micro and small business sector. This study uses a quantitative approach with secondary data analysis methods sourced from the financial reports of related institutions. The analysis techniques used include financial ratios such as Return on Asset (ROA), Return on Equity (ROE), Non-Performing Financing (NPF) for LKMS, and Non-Performing Loan (NPL) for conventional microfinance institutions. Data processing is carried out using descriptive statistical tests and comparative analysis to identify significant differences between the two systems. This study provides a deeper perspective by integrating aspects of operational efficiency and financial resilience in comparing the two types of microfinance institutions. In addition, this study highlights the role of sharia principles in risk management and its impact on the financial stability of related institutions, an approach that is still limited in previous studies. The research findings show that LKMS have a relatively stable level of profitability despite experiencing challenges in managing liquidity due to limited sources of sharia-based funding. On the other hand, conventional microfinance institutions tend to be more flexible in accessing capital but face higher credit risk. Overall, sharia-based financing mechanisms show better resilience in maintaining a balance between financial sustainability and financing risk.Keywords: Financial performance, sharia microfinance institutions, conventional microfinance institutions, profitability, credit risk, liquidity.